CORREIA, Marlene de Castro. Drummond: A Magia Lúcida. Rio de Janeiro, Zahar, 2002. - Silva, Mauricio (Organon, 2003)
CORREIA, Marlene de Castro. Drummond: A Magia Lúcida.Rio de Janeiro, Zahar, 2002.Resenhado por: Maurício Silva